Effect of inorganic species on torrefaction process and product properties of rice husk. (October 2018) - Zhang, Shuping; Su, Yinhai; Ding, Kuan; Zhu, Shuguang; Zhang, Houlei; Liu, Xinzhi; Xiong, Yuanquan
Highlights: Effect of inorganic species on torrefaction product properties was evaluated. Inorganic species have significant effect on torrefaction process. Leaching process slightly reduced the volume concentration of CO2 in gas product. Removal of AAEMs slightly increased organic component content in liquid product. AAEMs enhanced the deoxygenation and dehydrogenation during torrefaction process. Abstract: The objective of this study was to evaluate the effect of inorganic species on torrefaction process and product properties. Torrefaction process of raw and leached rice husk was performed at different temperatures between 210 and 270 °C. Inorganic species have significant effect on the torrefaction process and properties of torrefaction products. The results indicated that solid yield increased, gas yield decreased and liquid yield remained unchanged for leached rice husk when compared to raw rice husk. Gas products from torrefaction process mainly contained CO2 and CO, and leaching process slightly reduced the volume concentration of CO2 . Removal of inorganic species slightly decreased water content and increased organic component content in liquid products. Acetic acid, furfural, 2, 3-dihydrobenzofuran and levoglucosan were the dominant components in liquid product. Inorganic species enhanced the effect of deoxygenation and dehydrogenation during torrefaction process, resulting in the enrichment of C component in solid products.